Don’t jump to conclusion – priapism in acute spinal cord injury: a case presentation - Yusof, M. R.; Afiq, O.; Khairul-Asri, M. G. (Izdatel'skii Dom A B V-Press, 2022)
Priapism is an uncommon urology emergency. However, if detected late and not classified correctly and treatment not appropriately given can cause necrosis and fibrosis of penis. This will lead to permanent erectile dysfunction and can be devastating to patient. Literature of Spinal Cord Injury with priapism is rare and not many reported. We have a case of young gentleman with priapism secondary to spinal cord injury. It was detected early and treated promptly and patient had good outcome with no evidence of permanent erectile dysfunction.